Phonology awareness as a process of teaching English to children with sen (special educational needs) in La Salle - Conocoto High School. - Sánchez Córdova, Mónica Jacqueline (2022)
Teaching English as a foreign language has involved a series of complications and limitations in the development of its learning and practice due to the applied strategies and methodologies; the new generations are born in a world of technology and therefore the use of a different language is essential to be an active part of the society; not forgetting that the family, the school and the community are the primary sources of learning to identify the utility of teaching Speech Sounds as part of Phonology Awareness considered as a strategy to teach EFL to children with dyslexia and autism. This research was based on a qualitative investigation in which the researcher collected and analyzed data to understand opinions and experiences about Speech sounds because it was relevant to investigate the different kinds of SEN that students presented in each classroom and the attitude they would show at the end of the investigation. The technique used was the observation to verify the oral production, instruments like pre-test and post-test were applied to the students, to obtain numbered data, so that it can be analysed, explained and interpreted to accept or reject the hypothesis. This research was based on a group of 27 students from ninth and tenth grades who presented ASD (Autism Spectrum Disorder) that is not associated to the disability and DL (Dyslexia) that is a Specific Learning Disorder not associated to the disability also, from which 23 students identified and distinguished the correct use of the language sounds while 4 students were not able to develop writing and reading skills in Phonology using the language sounds but they could learn and understand that English has special pronunciation and it is important to learn its sounds. The results of this study showed that the phonological awareness program was effective in improving the Word Recognition Ability of children in experimental group, the results also indicated that children with Autism Spectrum Disorder who did not received any formal reading instruction were capable of improving their Word Recognition Ability in preparation for their future reading.